If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 12 + -2x Solving 4 = 12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4 + 2x = 12 + -2x + 2x Combine like terms: -2x + 2x = 0 4 + 2x = 12 + 0 4 + 2x = 12 Add '-4' to each side of the equation. 4 + -4 + 2x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 12 + -4 2x = 12 + -4 Combine like terms: 12 + -4 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 5y^2+11y-12=0 | | x+10+-24=0 | | 3y^2-5y-12=0 | | 5y^2+4y-1=0 | | (8x^2-5x^3)-(2x^2-9x^3)= | | (5x-8)(3x+9)= | | 3a=1-6c | | 3a+6c=1 | | y^2+16y+13=0 | | x-4=6x-15 | | [x+10(27-x)]+[10x+27-x]=9 | | 16a-4=6a-34 | | 8x-3(3x+4)=11 | | x^2+x-15=0 | | 7k+2=4k-25 | | 5x+9=8x+33 | | 4y-7=8y-23 | | 7h-6=2h-21 | | 2p+3=p-4 | | 123+3= | | 2p+3=-4 | | 8x+5=14-x | | 5+6x=25+x | | 12-6=8p-2 | | 7d=-2-18 | | 3a=20-2a | | 7d-2=-2 | | 4y-7=-3 | | 2(x-3)+5(x+2)=4(x-1)+3 | | 4m+1=-3 | | 4-3(2x+5)=5-(x-3) | | 12x+y=16 |